Sociodemographic Background Predisposing Youths into Gang Violence in Lagos Metropolis, Nigeria - Ogunmefun Folorunsho Muyideen; Aborisade A. Richard; Atere Adewole (RIRAI Publisher, 2024)
The historical and constitutional responsibility of youths in any country cannot be underrated because youth remain one of the vital weapons for accelerating and harmonizing societal orderliness Evidence gathered from extant publication shows that youth formed the larger percentage of people apprehended for violence activities in most correctional facilities in the world. In Nigeria, Extant publications were reviewed while Anomie and rational choice theories were adopted for the study. Mixed methods were adopted for collections of data from the inmates in the Lagos correctional facility approved for the study400 hundred copied of structured questionnaires in the three approved corrections in Lagos But 347 of the questionnaires were retrieved for the quantitative analysis while 36 out of 40 interviews conducted were found useful using In-depth interview for the inmates while key informant interviews were used for collection of verbal data from the member of the Nigeria Police Force, Correctional Officers, market men/women and community elders in Lagos. The concluded that gender positioning (t-047), family background (t-=083) and marital status (t=014) significantly predisposed youths into violent activities compared with employment (t= 816), age (t=123) and level of education (t=482). In addition, the qualitative data indicated that immaturity and poor parental background influence youth gang violence. The social interventionist should encourage the family, youths and community members to get involved in decision making, adequate youth development programme should be encouraged and youth should develop act of self-creativity and innovation toward promoting self-image in Nigeria